Rancang Bangun Sistem Manajemen Inventaris Barang Pada Toko Wijaya Toys Berbasis Web Menggunakan Framework Codeigniter - Simanullang, Mastiur; Randi Rian Putra; Winda Erika (Jurnal Mahajana Informasi, 2024)
This research aims to design and implement a web-based inventory management system for the Wijaya Toys Store using the CodeIgniter framework. Wijaya Toys Store is a trading business that sells various kinds of toys and children's equipment. The system developed aims to increase efficiency in stock management, make it easier to record sales transactions, and provide accurate and real-time reports to management. The choice of the CodeIgniter framework as the basis for developing this system was based on its ability to provide a structured and easy to understand MVC (Model-View-Controller) structure. The research methods used include user needs analysis, web-based system design, implementation using the latest technologies, and testing to ensure system performance and reliability. The result of this research is a web application that not only simplifies the process of managing stock, but also increases the accuracy of inventory data at the Wijaya Toys Store. This system is expected to reduce recording errors, minimize stock losses, and enable management to make more appropriate decisions based on the data collected.